Granulomatous Mastitis: Imaging of Temporal Evolution - Ahmed Bilal; Fahad Badar Albadar; Nauman Bashir Barlas (Scientifica)
Aim. To assess the temporal imaging evolution of granulomatous mastitis and to review imaging findings. Material and Methods. Retrospective review of imaging data of 10 patients with biopsy proven granulomatous mastitis. The patients were divided into 3 groups according to their initial imaging presentation. Temporal evolution of imaging findings was observed separately for each group. Ratios, proportions, and percentages were used for data analysis. Results. Upon initial presentation, 75% of women who underwent mammogram showed an area of mass like architectural distortion. 25% demonstrated focal asymmetry. Complex cystic lesion was seen 40%. Multiple abscesses with sinus tract formation tracking into surrounding tissues were seen in 2 cases. Four out of 10 patients presented as edematous changes. Three out of this group progressed to develop complex cystic lesions/abscess formation. 25% presenting with complex cystic lesions or abscess at presentation showed spontaneous resolution. The remainder needed surgical treatment. The patients with abscess formation and sinus tract formation needed surgical management. Conclusion. Initial imaging findings in granulomatous mastitis can be variable but the eventual course and outcome is similar in most patients with surgical management required in most cases.